2016
DOI: 10.1002/anie.201608013
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Coupling Reaction of Quinone Monoacetal with Phenols Leading to Phenol Biaryls

Abstract: A simple and efficient synthesis of phenol biaryls by the cross-couplings of quinone monoacetals (QMAs) and phenols is reported. The Brønsted acid catalytic system in 1,1,1,3,3,3-hexafluoro-2-propanol was found to be particularly efficient for this transformation. This reaction can be extended to the synthesis of various phenol biaryls, including sterically hindered biaryls, with yields ranging from 58 to 90 % under mild reaction conditions and in a highly regiospecific manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…In contrast, fast proton exchange was not observed between TfOH and the OH proton of 1 b (H n ); nor was the signal corresponding to the methylene protons of 1 b (H m ) observed to shift during the titration, indicating that TfOH preferentially donates H‐bonds to HFIP rather than 1 b . Mixed ethers resulting from dehydrative condensation of HFIP and 1 b were not observed, ruling out the possibility that HFIP ethers serve as a reservoir of benzylic cations . However, in the absence of arene nucleophile, ethers resulting from the dehydrative dimerization of 1 b were observed to form in small quantities when higher catalyst loadings (>40 mol % TfOH) were employed.…”
Section: Figurementioning
confidence: 99%
“…In contrast, fast proton exchange was not observed between TfOH and the OH proton of 1 b (H n ); nor was the signal corresponding to the methylene protons of 1 b (H m ) observed to shift during the titration, indicating that TfOH preferentially donates H‐bonds to HFIP rather than 1 b . Mixed ethers resulting from dehydrative condensation of HFIP and 1 b were not observed, ruling out the possibility that HFIP ethers serve as a reservoir of benzylic cations . However, in the absence of arene nucleophile, ethers resulting from the dehydrative dimerization of 1 b were observed to form in small quantities when higher catalyst loadings (>40 mol % TfOH) were employed.…”
Section: Figurementioning
confidence: 99%
“…Fluoroalcohols, such as 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) and 2,2,2-trifluoroethanol (TFE), possess specific properties that differentiate them from other non-fluorinated alcohols; they are highly polar [28] and weakly nucleophilic [29] and exhibit remarkable hydrogen-bond donor abilities [30]. Owing to their unique physical properties, these fluoroalcohols can dramatically direct the course of reactions; thus, as a means of developing new reactions, the authors utilized HFIP and TFE as attractive and distinctive alternatives to ordinary solvents in hypervalent iodine chemistry [31,32,33]. In these studies, we unexpectedly discovered the metal-free S N Ar-type arylation of heteroaromatic diaryliodonium salts by nucleophilic aromatic compounds facilitated by Lewis and Brønsted acids, i.e., boron trifluoride, trimethylsilyl triflate, and triflic acid (TfOH), in fluoroalcohols [34,35,36].…”
Section: Resultsmentioning
confidence: 99%
“…In the latter case, the nucleophilic substitution reaction was the cause of the regioselectivity (Scheme 20). [66] …”
Section: Reactions Of Para‐quinols and 25‐cyclo‐hexa‐dienone Monoketalmentioning
confidence: 99%
“…In the latter case, the nucleophilic substitution reaction was the cause of the regioselectivity (Scheme 20). [66] Further, Saziki et al demonstrated the FeCl 3 catalyzed Friedel-crafts arylation reaction of 4-aryl-4-methoxy-2,5-cyclohexadienone 177 which gave the compound 178 in a highly regioselective manner. It was further arylated through dearomatization and arylation reactions on compound 177 gave substituted phenol 179 in few steps (Scheme 20).…”
Section: Reactions Of Para-quinols and 25-cyclo-hexa-dienone Monoketalmentioning
confidence: 99%